Piloting the Perception of Talented Students and Parents about an Inclusive Activity: Pilotaje de la percepción de estudiantes talentosos y padres de familia sobre una actividad inclusiva (Papeles, 2024)
Introduction: Achieving an inclusive school is one of the challenges of educational systems to promote a personalized and satisfactory education for all from institutional educational projects. The third Cuban educational improvement is committed to inclusive education in which students with academic talent must be considered. To do this, the opinion of the students and their families who will be the protagonists of the new changes must be considered. For these reasons, the objective of this article is to present the results of the perception of five talented students and their families, regarding the way in which they are included in the “Eduardo García” pre-university institute in the city of Cienfuegos, Cuba, after participate in an extra-teaching activity aimed at developing the script for an educational video on induced electric current. Methodology: The methodological approach is qualitative, exploratory and diagnostic based on a single case study. Results and discussion: The perception of the inclusion of the five talented students and their family after carrying out the activity is investigated. The results showed that students are motivated by these types of activities and that parents consider them beneficial. Conclusion: It was detected that planned work must be done with the group of teachers and the family to achieve better conditions of inclusion.
Keywords: Academic talent; inclusion; perception; educational attention